Rush: clockwork angels tour [videorecording (DVD)] (Anthem Film & Television Productions, 2013)
Shown from a unique point-of-view, utilizing distinct composition and a voyeuristic style that, at varying moments, puts the viewer on the stage, at the side of the stage, and throughout the arena. The concert features over three hours of music, including favorites, Tom Sawyer and The Spirit of Radio, three drum solos, new string arrangements of classics, and rarely-performed songs.